Análise de dados piezométricos de um aterro sobre argila mole com drenos verticais - Ferreira, Carlos Alberto Moreira (1991)
The purpose of this dissertation is to analyse piezometers data from Trial Embankment II of IPR-DNER on Sarapui’s soft clay with vertical drains. Initially, the excess poro pressure data from installed Casagrande and Hydraulic piezometers of all the sections are analised and compared. Follows a bibliographical revision of the theory of vertical drains, including a description of the method used to obtain coefficients of consolidation from excess pore pressure data. The results of coefficients of consolidation back calculated with the above method are compared with others previously obtained. Finally, the performance of each vertical drain is analysed, being concluded that sand drains, with a special reference to jetted drains, were the most efficient.